2009
DOI: 10.1002/pro.157
|View full text |Cite
|
Sign up to set email alerts
|

Fusion order controls expression level and activity of elastin‐like polypeptide fusion proteins

Abstract: We have previously developed a method to purify recombinant proteins, termed inverse transition cycling (ITC) that eliminates the need for column chromatography. ITC exploits the inverse solubility phase transition of an elastin-like polypeptide (ELP) that is fused to a protein of interest. In ITC, a recombinant ELP fusion protein is cycled through its phase transition, resulting in separation of the ELP fusion protein from other Escherichia coli contaminants. Herein, we examine the role of the position of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 36 publications
7
57
0
Order By: Relevance
“…1a), which are similar in composition to I48S48 (Table 1). The DNA sequence of FKBP was inserted to the N-terminus of the ELP, where superior protein activity has been reported [24]. DLS demonstrated that FSI fusion proteins assembled particles with a 23.8 nm hydrodynamic radius (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1a), which are similar in composition to I48S48 (Table 1). The DNA sequence of FKBP was inserted to the N-terminus of the ELP, where superior protein activity has been reported [24]. DLS demonstrated that FSI fusion proteins assembled particles with a 23.8 nm hydrodynamic radius (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The fused ELP component of PODs enabled their facile, chromatographyfree purification by inverse transition cycling (ITC) (Fig. S2) (24), with yields of ∼150 mg/L of purified PODs in a shaker flask culture. By tuning the composition of the ELP, we were able to create GLP-1 PODs with a T t below body temperature (POD forming, ELP Low ) or above body temperature (soluble control, ELP High ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, 1.2 mg CAD was obtained from 100 ml culture, less than P. pastoris and B. subtilis. It was reported that placing the ELP at the N-terminus of the target protein decreased the expression level of the ELP fusion proteins, probably due to the fact that this placement increased the fraction of misfolded protein that are more likely to be degraded by E. coli proteases during intracellular translation [19]. In this study, CELP was fused at the N-terminus of CAD; otherwise there would be one or two extra amino acid residues left on CAD which might decrease the antimicrobial activity of the peptide [20].…”
Section: Discussionmentioning
confidence: 99%